Distribution and speciation of heavy metals in sediments at Caijiawan region - Meizhou, Mao; Zihui, Liu; Huiru, Dong; Jingyi, Liu; Schmitz, Wilfried; Ramezanian, Navid; Müller, German (Journal of environmental sciences (China), 1992)
Metals in different fractions in samples from surface sediments，cores，riverbank soil，islet soil and agricultural soil at Caijiawan were determined．The effect of particle size，density gradient on metal accumulation in sediments were studied．The chronology of core samples indicated that the pollution history corresponded to the development history of Dexing Copper Mine．;Metals in different fractions in samples from surface sediments，cores，riverbank soil，islet soil and agricultural soil at Caijiawan were determined．The effect of particle size，density gradient on metal accumulation in sediments were studied．The chronology of core samples indicated that the pollution history corresponded to the development history of Dexing Copper Mine．
Gesehen am 29.03.2023